Workforce Analysis from an Accounting Perspective: What Do the Determinants Really Demand? - Tuğba Koç; Bilge Katanalp; Adem Akbıyık (Istanbul Business Research)
Each profession has its own criteria. Of all the management disciplines, the employment trend in the field of accounting best reflects the state of recruitment of professionals. Thus, we need to examine what each profession expects from accountants. Using text analysis via Wordstat, we analyze 7,320 pre-accounting job advertisements to find the overall job specification of the sector for a pre-accounting employee. Of the 25 criteria identified, 12 were found common in the literature, local standards, and the sector. From our findings, the Turkish sector is more adapted to international than local standards, indicating that local standards were set without consulting the employers. This study further confirms that soft skills are as important as technical skills. Additionally, women are more likely to be recruited to a pre-accountant position during their 10-year study period. Turkey is a Eurasian country that is influenced by both Asian and European countries and their respective profession-related norms and practices. Thus, our findings may be generalizable. Overall, policymakers need to pay attention to the employers’ opinions before establishing local standards.